Light in the Darkness: Responses to Light and Diel Activity Rhythm in an Eyeless Cave Flatworm (Dendrocoelum italicum) - Benedetta Barzaghi; Raoul Manenti; Gentile Francesco Ficetola; Roberta Pennati; Andrea Melotto (Ecology and Evolution, 2025)
ABSTRACT Troglobiont species show common traits derived from adaptation to subterranean life. Due to lack of light in cave environments most troglobiont species show eye reduction or even loss, often accompanied by a disruption of diel rhythmicity. Although cave adaptation and eye absence generally imply the loss of capability to perceive light, several cave‐adapted species have retained this function, showing some degree of phototaxy or rhythmicity. Flatworms are ubiquitous in natural habitats and the response to light or diel rhythmicity of surface‐dwelling species has received considerable scientific attention in the past and is increasingly studied. Conversely, responses to light stimuli have been poorly investigated in eyeless troglobiont flatworms. Here we coupled field monitoring and behavioural experiments to investigate phototactic responses and variation in diel activity patterns in the troglobiont eyeless flatworm Dendrocoelum italicum. We tested 27 D. italicum individuals from ‘Bus del Budrio’ cave, measuring their response to light stimuli in a semi‐obscured experimental arena under different light‐exposure treatments: dim light, bright light and darkness. Besides, during a 2‐year period we conducted 18 visual‐count surveys to monitor daytime and nighttime flatworm abundance in the cave. Behavioural tests showed that flatworms selected the darker side of the arena under both bright and dim light exposure, revealing a marked negative phototaxis. Field surveys revealed that flatworm abundance was significantly affected by the diurnal cycle, with a higher number of individuals visible during the night. These outcomes offer interesting insights on adaptation to cave environments, showing that key functions, such as the capability to respond to light or diurnal cycles, can be retained in troglobiont species and call for future investigation assessing the potential adaptive roles of these traits in mediating their exploitation of subterranean environments or their interface with the surface. Besides, this study proposes an effective in‐field method for conducting studies on subterranean fauna responses to light stimuli.